Effect of deposition cycles on the properties of ZnO thin films deposited by spin coating method for CZTS-based solar cells - Shafi, Muhammad Aamir; Bouich, Amal; Fradi, Khawla; Guaita, Julia Mari; Khan, Laiq; Mari, Bernabe (Optik (Stuttgart), 2022)
The spin-coating technique was used to make ZnO thin films in this study. To get various thicknesses of ZnO thin film on FTO substrate, the numbers of spin coatings were changed, 2,4,6,8, and 10 times. The polycrystalline character of the ZnO film can be seen in all of the XRD samples. The more strong peaks exist on (100), (002) and (101) at two theta degrees 34.14, 34.84 and 36.68, respectively. The effect of different deposition cycles was evaluated based on the surface homogeneity. The ZnO deposited by 8 and 10 cycles showed a dense and smooth surface with good crystallinity and roughness with no holes. The estimated band gap for as-deposited ZnO films is 1.73–2.35 eV with increasing deposition cycles. As we annealed the samples at 450ºC for 45 min, the variation in the band was observed from 3.24 to 3.29 eV. Hence the annealing also played an essential role in the band gap variation. To check the effect of cycles on solar cell performance, a simulation software SCAPS-1D was used. We proposed a solar cell of model “Back.Contact/CZTS/CdS/ZnO/Front.Contact/Glass” used in the simulation. [Display omitted]